2019
DOI: 10.1371/journal.pntd.0007132
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes and prognostics of visceral leishmaniasis in HIV infected patients with use of pentamidine as secondary prophylaxis based on CD4 level: a prospective cohort study in Ethiopia

Abstract: Background The long-term treatment outcome of visceral leishmaniasis (VL) patients with HIV co-infection is complicated by a high rate of relapse, especially when the CD4 count is low. Although use of secondary prophylaxis is recommended, it is not routinely practiced and data on its effectiveness and safety are limited. Methods A prospective cohort study was conducted in Northwest Ethiopia from August 2014 to August 2017 (NCT02011958). HIV-VL patients were followed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
(38 reference statements)
2
24
0
Order By: Relevance
“…Malnutrition and HIV infection are the most significant comorbidities because they increase host susceptibility, are determinants for severity and clinical manifestations of the leishmaniases, and complicate accurate diagnosis and treatment. 25,85,[91][92][93] For instance, case-controlled research in Ethiopia has shown a three-fold increase in susceptibility to VL in malnourished individuals. 94,95 Additional research is needed to understand the impact of nutritional deficits on vector competence.…”
Section: Comorbidities Synergistically Act With Poverty To Exacerbate the Leishmaniasesmentioning
confidence: 99%
“…Malnutrition and HIV infection are the most significant comorbidities because they increase host susceptibility, are determinants for severity and clinical manifestations of the leishmaniases, and complicate accurate diagnosis and treatment. 25,85,[91][92][93] For instance, case-controlled research in Ethiopia has shown a three-fold increase in susceptibility to VL in malnourished individuals. 94,95 Additional research is needed to understand the impact of nutritional deficits on vector competence.…”
Section: Comorbidities Synergistically Act With Poverty To Exacerbate the Leishmaniasesmentioning
confidence: 99%
“…In Ethiopia, over 50% of VL/HIV co-infected patients will experience relapse of VL between 3 and 9 months post anti-leishmania treatment (12). The mechanisms accounting for the increased rate of VL relapse in VL/HIV co-infected patients are poorly characterised.…”
Section: Introductionmentioning
confidence: 99%
“…Little work has been done to investigate drug resistance markers in African visceral leishmaniasis, where drug resistance is not thought to be a significant clinical problem (Gidey et al 2019), and no genetic markers have -to our knowledge -been identified in the region. Identifying such resistance in recurrent VL/HIV would be complicated by the complex history of drug exposure for many of these patients, as clinicians frequently resort to second-line drugs or combinations in an attempt to improve treatment outcomes (Diro et al 2019;Monge-Maillo and López-Vélez 2016;Mohammed et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia and elsewhere, HIV coinfection is known to increase the probability that L. donovani infections progress to symptomatic visceral leishmaniasis (Hurissa et al 2010;Albuquerque et al 2014). These co-infections are difficult to treat, with poor clinical outcomes for patients with very high mortality and high rates of relapse following treatment (Hurissa et al 2010;Diro et al 2019;Alemayehu, Wubshet, and Mesfin 2016;Diro et al 2014;Mohammed et al 2020). It is generally thought that cure of VL is not sterile, so that parasites continue to be present, but there is little direct evidence of this.…”
Section: Introductionmentioning
confidence: 99%